A Game Development to Promote Computational Thinking - Waraporn Prompolmaueng; Apisit Wetmaha; Pornsuree Jamsri (My University, 2021)
This paper focuses on game development using Mixed Reality technology, the Magic Leap One device, by exploring with The Lab and Unreal Engine program that are developed in game interpolating Computational Thinking (CT). The research device focuses on integrating thinking skills into 3D games with real-time user interaction. From mixed reality (MR) the application of technology is evaluated in its use for learning effectiveness. The game aims to promote a computational thinking process based on the terms and conditions within 5 levels as well as the complexity of the game with more obstacles in each level as the character travels from beginning to destination. Commands provide for different contexts. Major goal is using mixed reality technology to advance convergence in computing education and training in computational thinking (CT) to help players strengthen their thinking process and CT through the game. This game can be an alternative learning medium for the educator in primary school (Grade 4–6). The assessment of target users 10–15 persons before and after the game tests have 3 aspects in technology, CT, and usability of game performance. An expert evaluation was conducted after the test. Assessment of the overall game focuses on building of CT skill within the game relative to project objectives. Evaluation results were 77.8% by users and 88.6% by the expert. Furthermore, some useful suggestions from assessment suggest adding workshop guidelines for educators or trainers. Thus, this project contributes to the computing education community by using available cutting-edge technology as an optional teaching tool in CT that suits learners in education at the primary level and looks toward future development for higher education.
Keywords: Teaching and Learning Programming; Educational Games and Gamification; Augmented Reality Applications